2021
DOI: 10.31557/apjcp.2021.22.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Survival after Laparoscopic versus Abdominal Radical Hysterectomy in Early Cervical Cancer: A Randomized Controlled Trial

Abstract: Background: Previous studies have reported the safety of laparoscopic radical hysterectomy for treatment of early cervical cancer, as option to laparotomy. This study aims to compare overall survival between laparoscopic versus abdominal radical hysterectomy for early cervical cancer. Methods: A single-center randomized controlled trial enrolled 30 patients with clinically staged IA2 cervical cancer and lymphovascular invasion, IB and IIA, who underwent laparoscopic radical hysterectomy ( 16) or abdominal radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The pooled hazard ratio was 71% higher for patients having minimally invasive surgery in comparison with patients having open radical hysterectomy [ 18 ]. After the publication of the results of LACC trial, other studies observed similar findings, even in the population with tumor diameter < 2 cm [ 19 , 20 ]. However, another randomized prospective study (a part of the LACC trial [ 13 ]) compared minimally invasive and open radical hysterectomy [ 20 ].…”
Section: After the Lacc Trailmentioning
confidence: 70%
See 3 more Smart Citations
“…The pooled hazard ratio was 71% higher for patients having minimally invasive surgery in comparison with patients having open radical hysterectomy [ 18 ]. After the publication of the results of LACC trial, other studies observed similar findings, even in the population with tumor diameter < 2 cm [ 19 , 20 ]. However, another randomized prospective study (a part of the LACC trial [ 13 ]) compared minimally invasive and open radical hysterectomy [ 20 ].…”
Section: After the Lacc Trailmentioning
confidence: 70%
“…After the publication of the results of LACC trial, other studies observed similar findings, even in the population with tumor diameter < 2 cm [ 19 , 20 ]. However, another randomized prospective study (a part of the LACC trial [ 13 ]) compared minimally invasive and open radical hysterectomy [ 20 ]. This study enrolled only 30 patients (including 16 and 14 laparoscopic and open radical hysterectomy, respectively).…”
Section: After the Lacc Trailmentioning
confidence: 70%
See 2 more Smart Citations
“…The basic characteristics of selected studies are listed in Table 1 . Two studies were RCTs ( 12 , 29 ), and the remaining were observational studies ( 10 , 11 , 14 17 , 21 28 , 30 61 ) (n=46). Three treatment modalities were adopted by contrast: MIS (laparoscopic radical hysterectomy plus robot-assisted radical hysterectomy) versus ARH (n=10), laparoscopic radical hysterectomy versus ARH (involved 31 studies), and robot-assisted radical hysterectomy versus ARH (involved 10 studies).…”
Section: Resultsmentioning
confidence: 99%